The Bioinformatics Analysis of Comparative Genomics of Mycobacterium tuberculosis Complex (MTBC) Provides Insight into Dissimilarities between Intraspecific Groups Differing in Host Association, Virulence, and Epitope Diversity - Jia, Xinmiao; Yang, Li; Dong, Mengxing; Chen, Suting; Lv, Lingna; Cao, Dandan; Fu, Jing; Yang, Tingting; Zhang, Ju; Zhang, Xiangli; Shang, Yuanyuan; Wang, Guirong; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Tuberculosis now exceeds HIV as the top infectious disease cause of mortality, and is caused by the Mycobacterium tuberculosis complex (MTBC). MTBC strains have highly conserved genome sequences (similarity > 99%) but dramatically different phenotypes. To analyze the relationship between genotype and phenotype, we conducted the comparative genomic analysis on 12 MTBC strains representing different lineages (i.e., Mycobacterium bovis; M. bovis BCG; M. microti; M. africanum; M. tuberculosis H37Rv; M. tuberculosis H37Ra, and six M. tuberculosis clinical isolates). The analysis focused on the three aspects of pathogenicity: host association, virulence and epitope variations. Host association analysis indicated that eight mce3 genes, two enoyl-CoA hydratases, and five PE/PPE family genes were present only in human isolates; these may have roles in host-pathogen interactions. There were 15 SNPs found on virulence factors (including five SNPs in three ESX secretion proteins) only in the Beijing strains, which might be related to their more virulent phenotype. A comparison between the virulent H37Rv and non-virulent H37Ra strains revealed three SNPs that were likely associated with the virulence attenuation of H37Ra: S219L (PhoP), A219E (MazG) and a newly identified I228M (EspK). Additionally, a comparison of animal-associated MTBC strains showed that the deletion of the first four genes (i.e., pe35, ppe68, esxB, esxA), rather than all eight genes of RD1, might play a central role in the virulence attenuation of animal isolates. Finally, by comparing epitopes among MTBC strains, we found that four epitopes were lost only in the Beijing strains; this may render them better capable of evading the human immune system, leading to enhanced virulence. Overall, our comparative genomic analysis of MTBC strains reveals the relationship between the highly conserved genotypes and the diverse phenotypes of MTBC, provides insight into pathogenic mechanisms, and facilitates the development of potential molecular targets for the prevention and treatment of tuberculosis.